Physical and psychological violence against infertile women - Zahra Moghadam; Hasan Ardabily; Mahvash Salsali; Fatemeh Ramezanzadeh; Saharnaz Nedjat (Tehran University of Medical Sciences, 2010)
Objective: To investigate the prevalence of physical and psychological violence against women with female factor infertility. Materials and methods: A total of 400 women with primary infertility attending the Vali-e-asr Reproductive Health Research Center in Tehran, Iran, were interviewed using the conflict tactics Scales (CTS2) questionnaire to investigate their experiences of physical and psychological violence. Results: The prevalence of psychological violence was 135 (33.8%), followed by physical 56 (14%). All women reported their husbands to be the perpetrators. Conclusion: Clinicians should identify the abused women and provide them with medical care and supportive counseling.